Targeting Results, Diagnosing the Means : Innovative Approaches for Improving Public Sector Delivery - Manning, Nick; Watkins, Joanna (World Bank, Washington, DC, 2016)
This note sets out approaches to reform which start with identifying the shortcomings in results and which then look for pragmatic solutions that fit the particular context: no best practice, fewer universal recommendations for institutional design. The relative merits of this type of approach have not been empirically tested, but they are nonetheless intuitively reasonable and offer an alternative to other models of institutional reform which have not had great success. This note argues that these results-based approaches are a welcome breath of fresh air in a difficult domain. They are clearly in tune with the current results focus of the international development community and they address many of the challenges recognized by practitioners in previous approaches. However the authors still have remarkably little hard evidence on which to base a robust assessment of the effectiveness of this type of intervention.